Do Diabetic Patients with Acute Coronary Syndromes Have a Higher Threshold for Ischemic Pain? - Nicolau,José Carlos (2014)
Background: Data from over 4 decades have reported a higher incidence of silent infarction among patients with diabetes mellitus (DM), but recent publications have shown conflicting results regarding the correlation between DM and presence of pain in patients with acute coronary syndromes (ACS). Objective: Our primary objective was to analyze the association between DM and precordial pain at hospital arrival. Secondary analyses evaluated the association between hyperglycemia and precordial pain at presentation, and the subgroup of patients presenting within 6 hours of symptom onset. Methods: We analyzed a prospectively designed registry of 3,544 patients with ACS admitted to a Coronary Care Unit of a tertiary hospital. We developed multivariable models to adjust for potential confounders. Results: Patients with precordial pain were less likely to have DM (30.3%) than those without pain (34.0%; unadjusted p = 0.029), but this difference was not significant after multivariable adjustment, for the global population (p = 0.84), and for subset of patients that presented within 6 hours from symptom onset (p = 0.51). In contrast, precordial pain was more likely among patients with hyperglycemia (41.2% vs 37.0% without hyperglycemia, p = 0.035) in the overall population and also among those who presented within 6 hours (41.6% vs. 32.3%, p = 0.001). Adjusted models showed an independent association between hyperglycemia and pain at presentation, especially among patients who presented within 6 hours (OR = 1.41, p = 0.008). Conclusion: In this non-selected ACS population, there was no correlation between DM and hospital presentation without precordial pain. Moreover, hyperglycemia correlated significantly with pain at presentation, especially in the population that arrived within 6 hours from symptom onset.